Ischemic (Low-Flow) Priapism Managed by Al-Ghorab Distal Corporoglanular Shunt - A Case Report - Muhammad Mahmud Ridho; Raden Danarto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Priapism is a rare urological condition characterized by a persistent penile erection unrelated to sexual stimulation, most commonly affecting adults, while in children it is frequently associated with sickle cell anemia or trauma. The Al-Ghorab shunt is an open distal shunt technique that may be utilized as a first-line surgical intervention. We report the case of a 58-year-old male who presented with a one-month history of painful persistent erection, with no history of sexual stimulation, medication use, or genital and perineal trauma. Based on clinical evaluation, the patient was diagnosed with ischemic (low-flow) priapism and was scheduled for open distal shunting using the Al-Ghorab (corporoglandular) shunt technique. The operative duration was 120 minutes, and the patient was managed postoperatively in a non-intensive care ward without complications, with an Erection Hardness Score (EHS) of 1. The patient was discharged on postoperative day five and returned for follow-up on postoperative day twelve, at which time the surgical wounds on the glans and ventral penis were noted to be dry, indicating that although surgical preference may vary among surgeons, the Al-Ghorab shunt can be considered as a first- or second-line option following percutaneous distal shunting based on its success rate and side-effect profile. Keywords: Ischemic Priapism, Low-Flow Priapism, Al-Ghorab Shunt, Distal  Corporoglanular Shunt.